Low level laser therapy for suprabony defects: A clinical study in India - Aishwarya Duble (Bioinformation, 2026)
Periodontal flap surgery effectively manages suprabony periodontal defects; however, adjunctive therapies may further improve healing and clinical outcomes. Therefore, it is of interest to assess the effectiveness of low-level laser therapy (LLLT) as an adjunct to flap surgery in 30 patients with chronic periodontitis. Clinical parameters, including plaque index, gingival index, probing pocket depth and clinical attachment level, were evaluated at baseline and after 3 and 6 months. Both groups showed significant improvement, whereas the LLLT group showed significantly greater reductions in plaque index, gingival index and probing pocket depth, together with greater clinical attachment level gain (p < 0.001). Thus, adjunctive LLLT enhances periodontal healing and improve the effectiveness of conventional periodontal flap surgery.